Impact of avatar facial anthropomorphism on body ownership, attractiveness and social presence in collaborative tasks in immersive virtual environments. (December 2021) - Dubosc, Charlotte; Gorisse, Geoffrey; Christmann, Olivier; Fleury, Sylvain; Poinsot, Killian; Richir, Simon
Abstract: Effective collaboration in immersive virtual environments requires to be able to communicate flawlessly using both verbal and non-verbal communication. We present two experiments investigating the impact of facial anthropomorphism on the sense of body ownership, avatar attractiveness, social presence and performance in two collaborative tasks. In the first experiment participants have to solve a construction game according to their partner's instructions using three avatars presenting different facial properties. Results reveal no significant difference in terms of body ownership and social presence, but demonstrate significant differences in terms of attractiveness and completion duration of the collaborative task. Unexpectedly, correlation analyses also reveal a link between attractiveness and performance. The more attractive the avatar, the shorter the completion duration of the game. Our second experiment was designed to investigate further the potential impact of the task carried out on the sense of social presence using the same avatars. While we observed a very high sense of social presence in both tasks (asymmetric collaboration and negotiation) with every avatar, our results did not reveal significant difference between the three conditions. However, we observed statistically significant differences between the two task types. The scores of the co-presence and of the perceived message understanding dimensions of social presence were higher during the negotiation task. The sense of social presence appears to be task sensitive, especially when non-verbal communication becomes more important during face-to-face interaction in immersive collaborative virtual environments. Graphical abstract: Highlights: Body ownership is not significantly impacted by facial anthropomorphism. Facial anthropomorphism of simple avatars impacts their perceived attractiveness. Avatar attractiveness and performance in collaborative tasks are correlated. Social presence is not significantly impacted by facial anthropomorphism. Social presence in collaborative virtual environments is task sensitive.